HUBUNGAN DUKUNGAN KELUARGA DAN EFIKASI DIRI DENGAN KEPATUHAN RESTRIKSI CAIRAN PADA PASIEN HEMODIALISIS DI RUMAH SAKIT ANANDA BEKASI : RELATIONSHIP OF FAMILY SUPPORT AND SELF-EFFICACY WITH FLUID RESTRICTION COMPLIANCE IN PATIENTS UNDERGOING HAEMODIALYSIS AT ANANDA BEKASI HOSPITAL - Rohayati, Rohayati; Umami, Ijah (STIKes Mitra Keluarga, 2025)
Introduction : The maintenance of quality of life for chronic renal failure (CKD) patients undergoing haemodialysis is dependent on adherence to fluid restriction. However, compliance levels are still low and are influenced by various factors, including family support and self-efficacy. This study aims to analyse the relationship between self-efficacy, family support, and compliance with fluid restriction in haemodialysis patients. Method: This cross-sectional study involved 86 haemodialysis patients at Ananda Hospital in Bekasi. Sampling was conducted using consecutive sampling. To assess respondent characteristics, family support, self-efficacy, and compliance with fluid restriction, we used instruments in the form of valid and reliable questionnaires. Data analysis used chi-square and Fisher's exact tests. Result: The majority of respondents were elderly (69,8%), unemployed (73,3%), and had a low level of education (43%). Most respondents had poor family support (53,5%), moderate self-efficacy (54,7%) and did not adhere to fluid restrictions (96,5%). There was no significant relationship between family support (p=1,000) or self-efficacy (p=0,419) with fluid restriction compliance. Conclusion: There was no association between family support or self-efficacy and adherence to fluid restriction in CKD patients undergoing haemodialysis. Further research is recommended to explore other psychosocial factors, such as spirituality and self-esteem.